HISTORICO-LEGAL AND SOCIOCULTURAL CAUSES AND THE IMPLICATIONS OF PEASANTS’ REVOLT AGAINST TAXATION IN IBADAN, WESTERN NIGERIA - Oyesola Animashaun (Malete Journal of Accounting and Finance, 2024)
The expectation that the Nigerian elites who were vested with political power at independence in 1960 would improve the lives of the populace appeared to be misplaced, because the nascent Nigerian state bounced from one avoidable social conflict to the other. One of the avoidable problems was the ill-conceived increase in the tax rate of the peasants by the Government of Western Nigeria in a period of economic depression. This article examines the reasons for the resistance to taxation, the legal and extra-legal ways by which the peasants were able to engage the military administration of Western Nigeria, albeit the Nigerian state laws enforcement machinery to a standstill, using the case study method. The article found that there were certain demographic similarities among the leaders of the agitation by a review of the existing literature. The rebellious peasants had their own legal order and communication system rooted in the Yoruba indigenous system. The article concluded that the violent agitation of the peasants began because of the refusal of the authority and the ruling elites to heed the pleas of the peasants through petitions and peaceful representations. The article therefore recommended that there is a need for the state authorities to understand the plights of the citizenry before imposing higher tax burden on them. Similarly, the different levels of governments in the Nigerian federation should learn from this experience in the formulation of current and future tax policies. Further, the Nigerian state’s resort to violence in this case was defeated in the face of popular revolt.